2017
DOI: 10.1021/acs.energyfuels.7b01995
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation for Pore Structure and CH4 Release Characteristics of Coal during Pulverization Process

Abstract: Qinshui coalfield is the largest coalbed methane and anthracite production base in China. In the process of mine gas prevention and control, there was a larger amount of gas that can be extracted, but even with this, the residual gas pressure is not up to standard. In this paper, in order to analyze its specific reasons, a series of experiments were carried out to investigate the pore structure, particle size distribution, and CH4 release characteristics of anthracite during the pulverization process. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The gas adsorption values at It also can be seen intuitively that the D s , D c , and D t diffusion coefficients in the open pore were larger than in the closed pore (Table 2). Si et al 29 discussed the diffusion coefficient division of pores on open and closed pores. They investigated that the value in open pores is much bigger than that in closed pores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas adsorption values at It also can be seen intuitively that the D s , D c , and D t diffusion coefficients in the open pore were larger than in the closed pore (Table 2). Si et al 29 discussed the diffusion coefficient division of pores on open and closed pores. They investigated that the value in open pores is much bigger than that in closed pores.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the pore geometry, 28 closed pores play a pivotal role in the process of gas seeping and transporting. 29,30 As well known, the closed porosity can impact the coal's reservoir nature. 31,32 The porosity is usually over 60% and even >80% for anthracite.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that when selecting powdered samples for LTNA experiments, the number of open pores in coal is increased during the pulverization process (Jin et al, 2016;Si et al, 2017). The quantity of nitrogen adsorbed by samples with small particle sizes in the LTNA experiment is greater, and the corresponding open pore volume is larger.…”
Section: Closed Pore Characteristics and Evolution Mechanism For Coal With Different Ranksmentioning
confidence: 99%
“…As shown in Figure 2, the fractures in coal provide the seepage channel for gas flow. For the CBM extraction, the gas flow in the fracture is controlled by the coal fracture permeability, which plays a significant role in gas recovery [5][6][7][8][9][10]. However, most of the coal seams belong to the low-permeability reservoirs, where gas cannot be produced economically without reservoir stimulation.…”
Section: Introductionmentioning
confidence: 99%